Terrestrial Fluids, Earthquakes and Volcanoes: The Hiroshi Wakita Volume III - Pérez, Nemesio M.; Gurrieri, Sergio; King, Chi-Yu.; Taran, Yuri.; SpringerLink (Online service) (Basel : Birkhäuser Basel : Imprint: Birkhäuser, 2008)
Terrestrial fluids, earthquakes and volcanoes: The Hiroshi Wakita volume III is a special publication to honor Professor Hiroshi Wakita for his scientific contribution to science, which has been closely linked with one of the major objectives of this 2008 International Year for the Earth Planet. Reducing natural risks in active tectonic and volcanic environments by searching and detecting early warning hydrological and geochemical signatures related to earthquakes and volcanic eruptions has been a major life research goal for Hiroshi Wakita. This third special issue of Pure and Applied Geophysics consists of 9 original papers written by researchers from Taiwan, Italy, Turkey, Iceland, USA, Sweden, India and Spain dealing with various aspects of the role of terrestrial fluids in earthquake and volcanic processes. It also includes a list of Hiroshi Wakita’s scientific publications. This volume III will be useful to students and professional researchers who are interested in the role of terrestrial fluids in earthquakes and volcanic activity.
Spatial and Temporal Changes of Groundwater Level Induced by Thrust Faulting -- Geochemical Monitoring of Geothermal Waters (2002–2004) along the North Anatolian Fault Zone, Turkey: Spatial and Temporal Variations and Relationship to Seismic Activity -- Coupling Between Seismic Activity and Hydrogeochemistry at the Shillong Plateau, Northeastern India -- Radon Changes Associated with the Earthquake Sequence in June 2000 in the South Iceland Seismic Zone -- CO2 Degassing over Seismic Areas: The Role of Mechanochemical Production at the Study Case of Central Apennines -- Changes in the Diffuse CO2 Emission and Relation to Seismic Activity in and around El Hierro, Canary Islands -- SO2 Emission from Active Volcanoes Measured Simultaneously by COSPEC and mini-DOAS -- Underground Temperature Measurements as a Tool for Volcanic Activity Monitoring in the Island of Tenerife, Canary Islands -- Carbon Dioxide Discharged through the Las Cañadas Aquifer, Tenerife, Canary Islands.
Keywords: Earth sciences; Earth Sciences, general